Comparison of digestive, immune and antioxidant enzyme activities of mackerel tuna (Euthynnus affinis) in the wild and under captivity. Issue 1 (1st January 2020) - Han, Mingyang; Zhou, Shengjie; Qin, Jian G.; Ma, Zhenhua; Yu, Gang
ABSTRACT: To explore the feasibility of land-based farming on mackerel tuna ( Euthynnus affinis ), the changes of antioxidant, immune and digestive enzyme activities of wild caught and indoor cultured juvenile mackerel tuna were evaluated. The activities of total superoxide dismutase, catalase, peroxidase and alkaline phosphatase in the liver of the wild group were significantly higher than those cultured under captivity. The total superoxide dismutase and peroxidase activities in the indoor cultured group were significantly increased in the head kidney, and the MDA content was significantly increased. The activities of lysozyme in the liver and head kidney, the activities of amylase, lipase and trypsin activities in the intestine were significantly increased in the indoor cultured group. The pepsin activity in the stomach was significantly reduced. The land-based farming increased the digestive enzyme activity compared to the wild caught group. The mode of land-based farming is suitable for growth and fattening of young fish, but it leads to inhibition of antioxidant capacity and increase in immune enzyme activity. This study adds knowledge of our understanding on the physiological response of mackerel tuna and improves future farming practice of this species in an indoor condition.